Radiological Management of Angiographically Negative, Spontaneous Intracranial Subarachnoid Hemorrhage: A Multicenter Study of Utilization and Diagnostic Yield. Issue 1 (30th May 2018) - Sadigh, Gelareh; Menon, Ranjith K; Bhojak, Maneesh; Aladi, Abather; Mossa-Basha, Mahmud; Wu, Lei; Lehman, Vance T; Brinjikji, Waleed; Dehkharghani, Seena; Derakhshani, Ahrya; Mossa-Basha, Feras; Allen, Jason W
Abstract: BACKGROUND: The optimal diagnostic evaluation for patients with angiographically negative subarachnoid hemorrhage (AN-SAH) remains controversial. OBJECTIVE: To assess the utilization rate and diagnostic yield of imaging tests routinely obtained in identifying a structural cause for AN-SAH. METHODS: In this retrospective multicenter study, consecutive adult patients admitted with nontraumatic, AN-SAH between 01/2010 and 12/2015 were included. Patients with intraparenchymal, subdural, or epidural hematomas in addition to SAH were excluded. Outcomes studied included utilization rate, diagnostic yield, and median time from admission for the following imaging tests: initial computed tomography angiography (CTA) and digital subtraction angiography (DSA), brain and cervical spine magnetic resonance imaging (MRI), and any repeat DSA or CTA performed either during initial admission or at long-term follow-up. RESULTS: A total of 752 patients were included (mean age, 53 yr; 54% male). Initial CTA and DSA were performed in 89% and 100% of patients, respectively. Brain MRI was performed in 75% of patients and was positive in 0.7% of cases. Cervical spine MRI was performed in 61% of patients and was positive in 0.2% of cases. Repeat, same-admission follow-up DSA and CTA were performed in 48% and 51% of patients and were positive in 3.3% and 1% of cases, respectively. Delayed follow-up DSA and CTA after discharge were performed in 26% and 7% of patients and were positive in 2% and 3.7% of cases, respectively, all with negative prior imaging studies. CONCLUSION: Cervical spine and brain MRI have extremely low diagnostic yield, both are commonly utilized in patients with AN-SAH; while repeat DSA and CTA are utilized less commonly and have slightly higher diagnostic yield.